(untitled) (Khairulummah, 2023)
This article has been written about the life and educational services of the Poet Abu Ula-Al Muarri, and the circumstances of life of the poet have been narrated in the article here it has been mentioned pertaining to his life. Things have been told regarding his lineage, his region and the reasons of his title. The incident of his childhood intelligence have been narrated in this article. Also, it has been indicated about poets he has studied. Apart from that, it has also been told in the article how treated with his poetry, and how he earned fame. This article has covered the account of a great poet, in short period and on limited pages. If we go through these few points, we can bring to the surface the important aspects of his whole life. Hence, it is a unique and conspicuous article.